Pediatric Chondromyxoid Fibroma-Like Osteosarcoma. (4th March 2017) - Stark, Matthew; Heinrich, Stephen D.; Sivashanmugam, Raju; Mackey, Dane; Wasilewska, Ewa; Craver, Randall
ABSTRACT: Chondromyxoid fibroma-like osteosarcoma (CMF-OS) is a low-grade osteosarcoma, often misdiagnosed on initial biopsy as a benign lesion, with five cases previously described. We report a 13-year-old male with an intramedullary lytic CMF-OS of the right tibial proximal metaphysis with cortical destruction and soft tissue extension. Diagnosis was based on malignant new bone formation, increased mitotic figures, lamellar bone permeation with bony destruction, and correlation with imaging studies. There were no metastasis at presentation and the tumor showed good response to standard chemotherapy with >95% necrosis.